2019
DOI: 10.1093/mnras/stz293
|View full text |Cite
|
Sign up to set email alerts
|

Neutron star collapse and gravitational waves with a non-convex equation of state

Abstract: The thermodynamical properties of the equation of state (EoS) of high-density matter (above nuclear saturation density) and the possible existence of exotic states such as phase transitions from nuclear/hadronic matter into quark-gluon plasma, or the appearance of hyperons, may critically influence the stability and dynamics of compact relativistic stars. From a theoretical point of view, establishing the existence of those states requires the analysis of the "convexity" of the EoS. We show indications of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 138 publications
(182 reference statements)
0
24
0
Order By: Relevance
“…unstable neutron stars. In the latter case, a compression shock can be formed at the inner border of the convex region and affect the gravitational collapse to a black hole, leaving imprints on gravitational waveforms, which would be of increased amplitude [75]. This result was shown to hold when using our Chiral Mean Field (CMF) EOS, but also other EOSs that did not include a deconfinement phase transition.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…unstable neutron stars. In the latter case, a compression shock can be formed at the inner border of the convex region and affect the gravitational collapse to a black hole, leaving imprints on gravitational waveforms, which would be of increased amplitude [75]. This result was shown to hold when using our Chiral Mean Field (CMF) EOS, but also other EOSs that did not include a deconfinement phase transition.…”
Section: Discussionmentioning
confidence: 72%
“…al. [75] presented interesting results from a systematic investigation of the convexity of equations of state (EOSs) 1 . In particular, they showed that non-convex thermodynamics, which can appear if the adiabatic index decreases sufficiently rapidly with increasing density, can affect the equilibrium structure of stable compact stars, as well as the dynamics of 1 We recall that fluids following convex EOSs are such that their fluid elements increase their specific volume and decrease their pressure when overtaken by a rarefaction wave (i.e., rarefaction waves are "expansive"); similarly, they are compressed when overtaken by a compression wave (i.e., compression waves are "compressive").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those observations are crucial for the detailed study of the matter state at several times of nuclear saturation density ρ 0 (with ρ 0 = 2 × 10 14 g/cm 3 ). Among them, the possibility of the existence of strange quark matter (SQM) in NSs' high-density cores is of special interest, and could be investigated with future Advanced LIGO/Virgo detectors (e.g., Miniutti et al 2003;Wei et al 2018;Aloy et al 2019;Bauswein et al 2019;Most et al 2019). For example, some studies (e.g., Aloy et al 2019) have shown that the loss of thermodynamic convexity of EOS (or the loss of monotonicity of the sound velocity c s ) could have direct imprints on both the dynamics of the collapse to black hole configurations and on the resulting gravitational waves.…”
Section: Introductionmentioning
confidence: 99%
“…[152][153][154][155][156], and can deliver an independent estimate of the EOS at densities exceeding the ones present in single NSs [157]. Therefore, the postmerger modelling also allows to investigate interesting phenomena such as phase transitions happening inside the merger remnant at very high densities [158][159][160]. It is expected that all BNS merger remnants which do not undergo prompt collapse, e.g.…”
Section: Introductionmentioning
confidence: 99%